2016
DOI: 10.1530/joe-16-0046
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-releasing peptide: a new tool for obesity treatment

Abstract: Obesity is an escalating epidemic, but an effective noninvasive therapy is still scarce. For obesity treatment, anorexigenic neuropeptides are promising tools, but their delivery from the periphery to the brain is complicated because peptides have a low stability and limited ability to cross the blood-brain barrier. In this review, we summarize results of several studies with our newly designed lipidized analogs of prolactin-releasing peptide (PrRP). PrRP is involved in feeding and energy balance regulation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 41 publications
(41 reference statements)
0
33
0
1
Order By: Relevance
“…As shown in our recent studies, lipidization of PrRP31 not only increased its stability but also enabled PrRP31 to accomplish a central anorexigenic effect both in mice and rats with DIO , Holubova et al 2016, Kuneš et al 2016. In our previous studies, DIO in mice was shown to be associated with high levels of leptin (Matysková et al 2008) and leptin resistance (Matyskova et al 2010).…”
Section: Discussionmentioning
confidence: 74%
“…As shown in our recent studies, lipidization of PrRP31 not only increased its stability but also enabled PrRP31 to accomplish a central anorexigenic effect both in mice and rats with DIO , Holubova et al 2016, Kuneš et al 2016. In our previous studies, DIO in mice was shown to be associated with high levels of leptin (Matysková et al 2008) and leptin resistance (Matyskova et al 2010).…”
Section: Discussionmentioning
confidence: 74%
“…PrRP and its receptor may represent a new promising target for obesity treatment [ 28 ]. Our previous studies have demonstrated that the lipidization of PrRP enables its central anorexigenic effects after peripheral administration in both acute and chronic experiments [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…185 Examples include gut include species of the genera Lactobacillus, Bifidobacterium, Lactococcus, Streptococcus, and Enterococcus. 186 There is increasing interest in exploring the beneficial features of next-generation probiotics or live therapeutic products which include species not traditionally considered as probiotics, such as Akkermansia muciniphila, 187 Faecalibacterium prausnitzii, 188 species of the genus Bacteroides, 189 and genetically modified Lactococcus strains carrying beneficial traits. 190 Recent evidence suggests that probiotic bacterial viability is not necessary to develop health-promoting effects in the host.…”
Section: Changing the Gut Microbiota Composition Via Probioticsmentioning
confidence: 99%